The Impact of the Covid-19 Pandemic on the Learning Process at Madrasah Tsanawiyah Negeri 1 Malang City - Muhammad Ibrahim; Aries Musnandar (Yayasan Adra Karima Hubbi, 2024)
The article aims to: 1) identify the implementation of online learning at MTs Negeri 1 Malang City during the Covid-19 pandemic, 2) identify the impacts that occur in online learning on teachers, students, and parents at MTs Negeri 1 Malang City during the Covid-19 pandemic, and 3) identify the reasons these impacts can occur in online learning on teachers, students, and parents at MTs Negeri 1 Malang City during the Covid-19 pandemic. This research is a qualitative research with a case study method approach. Respondents in this study were teachers, students, class VIII MTs Negeri 1 Malang City. Data collection used open-ended questionnaires, interviews, and documents. Data analysis in this study used qualitative descriptive analysis with the stages of data reduction, data display, and conclusion drawing/verification. The results of the study found that, 1) the implementation of online learning at MTs Negeri 1 Malang City during the Covid-19 pandemic has been implemented. 2) the implementation of online learning, each class makes a WA group, teachers, 3) the positive impact in online learning is getting new experiences from online learning, increased ability to technology, and more flexible time, 4) While the negative impacts related to the obstacles experienced include, among others, additional internet quota costs, internet network disruptions, limited mastery of technology, the completeness of the subject matter does not match the curriculum achievements.